2023
DOI: 10.2196/48254
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Health Students' Attitudes and Usage of ChatGPT in Jordan: Validation Study

Abstract: Background ChatGPT is a conversational large language model that has the potential to revolutionize knowledge acquisition. However, the impact of this technology on the quality of education is still unknown considering the risks and concerns surrounding ChatGPT use. Therefore, it is necessary to assess the usability and acceptability of this promising tool. As an innovative technology, the intention to use ChatGPT can be studied in the context of the technology acceptance model (TAM). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 96 publications
2
36
0
3
Order By: Relevance
“…The ndings of this study revealed that 85% of the participating university students have already used ChatGPT. An early study conducted during February-March 2023 among university students in health schools in Jordan reported that only 11% used ChatGPT at the time (Sallam et al 2023a). A subsequent multinational study that involved university students in ve Arab countries (Iraq, Kuwait, Egypt, Lebanon, and Jordan) during April-August 2023 reported ChatGPT usage at a rate of 25% (Abdaljaleel et al 2024).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ndings of this study revealed that 85% of the participating university students have already used ChatGPT. An early study conducted during February-March 2023 among university students in health schools in Jordan reported that only 11% used ChatGPT at the time (Sallam et al 2023a). A subsequent multinational study that involved university students in ve Arab countries (Iraq, Kuwait, Egypt, Lebanon, and Jordan) during April-August 2023 reported ChatGPT usage at a rate of 25% (Abdaljaleel et al 2024).…”
Section: Discussionmentioning
confidence: 99%
“…This study adopted a validated survey instrument based on the technology acceptance model (TAM) and speci cally tailored to measure the attitude towards ChatGPT among university students (Sallam et al 2023a). The survey instrument validity was con rmed in a recently published multinational study among university students in ve Arab countries (Abdaljaleel et al 2024).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This research endeavor is necessary to guide the ethical, responsible, and productive use of AI to enhance higher education guided by a robust scienti c evidence [14,16,17]. The relevance of the quest to meticulously examine the bene ts and challenges of AI in higher education is also important in light of the current evidence showing that a substantial number of university students are already using AI chatbots [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%